(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
This analysis has its genesis in the commitment of all Higher Education workers to help the integration process of the Cuban University be seen as a true potentiality. In addition, the systematic study of the result of this process is justified by the theoretical and practical importance of taking advantage of the strength it offers. Furthermore, and knowing that this process brought about a significant group of changes, reason in gab out an element that may appear as a factor of successor as a barrier is considered necessary: organizational culture. For this reason, this study seeks to analyze the management of organizational culture as a successful tool in the integration process of Cuban Higher Education. For this, an over view of the terms culture, organizational culture and its relationship with the integration of the Cuban university is given. The results of the analysis and the epidemiological situation of the country envisioned the need to respond to a more complex environment in order to improve the university model, which makes an appropriate understanding and management of the culture of higher education institutions unavoidable.